Relatórios dos presidentes, Época do Império, para serem inseridos (MEC-SEAC, Biblioteca Nacional, Servic̦o de Reprografia, 1970)
Includes provincial presidential reports from 6 provinces of Brazil, 1838-1889, including: Espírito Santo, 8 set. 1838; Goiás, 10 maio 1854; Paraíba, 24 junho 1838; Santa Catarina, 28 junho 1885; Piauí, 27 julho 1888; Pernambuco, 4 July 1854; and: Piauí, 23 July 1889.